Influence of website attributes on consumer’s online purchase intention in Malaysia - Adedoja, Omoloju Mariam; Hussin, Siti Rahayu; Wong, Foong Yee (Human Resource Management Academic Research Society Knowledge Words Publications, 2022)
Due to the global pandemic of COVID-19, the world has faced the difficulties in conducting business activities. The COVID-19 pandemic has interrupted shopping activities in Malaysia as consumers are steadily switching from offline to online purchases. Due to lockdown and social distancing, the closure of physical stores led consumers to shop via different websites in Malaysia. The research aimed to investigate the specific website attributes influencing consumers online purchase intention in Malaysia. An online survey was used to collect data from 384 respondents. For the purpose of this study, convenience sampling method was adopted. The questionnaire was designed on a five-point likert scale. The findings from the Pearson Correlation analysis showed that consumers intention to purchase via a website had a positive and significant relationship with website convenience (r=0.875, p<0.01), website speed (r= 0.863, p<0.05), website design (r=0.877, p<0.01), and website security (r= 0.871, p<0.05). The result of the regression analysis indicated that the model contributed a total of 79% and website design appears to be the most significant attribute that influence consumers’ intention to purchase online. Hence, the findings suggest that website managers should prioritize the interface of their website, including its structure and contents. This study further recommends future researchers to look into other attributes that could be affected by mediator variables such as cultures, religions, which are not tested in this study.